2011
DOI: 10.1111/j.1440-1843.2011.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of lung‐specific X protein mRNA in bronchial brushing specimens from patients with or without lung cancer

Abstract: Liquid-based cytology and RT-PCR can be performed to detect LUNX mRNA expression in bronchial brushing specimens, and this technique may be a useful adjunct to cytological diagnosis of lung cancer. The sensitivity of the technique was greater than that of cytology but its lower specificity should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The authors concluded that using more sensitive nonsequencing methods could alleviate the need for LCM. Similarly, Lv et al [27] successfully extracted mRNA for the detection of LUNX (lung-specific X protein) by RT-PCR from bronchial brushes collected in SurePath fixative.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that using more sensitive nonsequencing methods could alleviate the need for LCM. Similarly, Lv et al [27] successfully extracted mRNA for the detection of LUNX (lung-specific X protein) by RT-PCR from bronchial brushes collected in SurePath fixative.…”
Section: Resultsmentioning
confidence: 99%
“…This is the inverse of studies of mRNA expression of SPLUNC1 in the peripheral blood for the diagnosis of micrometastasis and the prognosis of lung cancer. (23,24) The reason may be related to the sensitivity of different methodology for protein and nucleic acid detection, though the higher protein levels of SPLUNC1 was determined in serum from lung cancer patients by our ELISA. A more sensitive method may need development for the detection from serum based on the MAbs.…”
Section: Discussionmentioning
confidence: 99%
“…(6) As an important addition to these, SPLUNC1 was also known as a potential marker for the detection of non-small lung cell cancer. (23,24) However, SPLUNC1 protein level investigations were lacking from NSCLC patients in the studies. In order to further explore the role of SPLUNC1 in lung cancer, a panel of specific MAbs was produced in our lab.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR can objectively detect even 1 cancer cell among 10 6 cells [18,19]. Identification of molecular markers for disease progression would be of great clinical value [20]. …”
Section: Discussionmentioning
confidence: 99%